Effect of epoxy resin as partial cement replacement on compressive strength and tensile strength with the fixed proportion of silica sand as partial sand replacement - Gan, Shang Wei (2018)
Structures are the elements that can be found in every country. Most of the structures are supported by the elements that made by concrete such as beam, column, slab and foundation. It play an important roles in withstand the loads from the upper elements which increase the stability and durability of the structures. The main material used in the mixtures to produce concrete is cement. The carbon dioxide was emitted in the process of cement production. As the development of the country increased, the coverage of urban area was increased. Hence, the usage of cement was increased. Therefore, making an effort to study the effect of the epoxy resin as the partial cement replacement in concrete on compressive strength and tensile strength is crucial. 30 numbers of concrete samples were prepared for the purpose of laboratory works. Compressive strength test and tensile strength test were used to determine the Compressive Strength and tensile strength of each sample in order to observe the optimum percentage of cement can be replace by epoxy resin to produce optimum strength. In this research, the 30% of cement was replaced by the epoxy resin gave the optimum compressive strength as well as tensile strength compare to 10% and 20% of the samples. The results of compressive strength recorded from this research varied from 5.96 to 29.17 MPa while the results of tensile strength recorded were varied from 1.26 to 2.23 MPa. The overall results of the samples show directly proportional when the percentage of the epoxy resin increased.